Assessment of the vestibuloocular reflex in fighter pilots with the video head impulse test. (July 2015) - Zuma e Maia, Francisco Carlos; Mangabeira Albernaz, Pedro Luiz; Cal, Renato; Brusco, Thaísa Rodrigues; da Costa, Sady Seleiman
Abstract Conclusion: There were no changes in the function of the six semicircular canals in active fighter pilots, through the use of the video head impulse test (vHIT). These results suggest that the vestibuloocular reflex (VOR) works well at the high frequencies related to the natural head movements in this population. Objectives/hypothesis: The vestibular function in pilots has been reported as being different from that of other normal subjects. These differences are attributed to adaptation of the vestibuloocular reflex (VOR) or by habituation. These studies were conducted with caloric and/or rotatory tests and were limited to the lateral semicircular canals. The aim of the present study was to verify the occurrence of high frequency changes in the function of the six semicircular canals in active fighter pilots, through the use of the video head impulse test (vHIT). Study design: Cross-sectional design. Methods: The subjects participating in this study were divided in three groups, according to their flight experience. The control group (Group 1) consisted of 20 soldiers with no experience of in-flight training. For the test subjects 14 fighter pilots were selected and divided into two groups. Group 2 included the pilots with 1000–2000 hours of flight experience and Group 3 included pilots with 2001–3000 hours of flight experience. They were all submitted to a video head impulse test and the gains of the six semicircular canals were analysed. Results: There were significantly low gain values (p < 0, 013) only in the left posterior semicircular canal in the control group as compared with the subject groups. However, there were no significant differences in gain values between the two groups of the active pilots.